Association Between Bile Reflux and Gastric Mucosal Damage Severity in Patients with Dyspepsia - Saturti, Tjokorda Istri Anom; Mariadi, I Ketut; Triyanayasa, I Nyoman; Sindhughosa, Dwijo Anargha; Kuwai, Toshio (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Bile acid reflux stands out as a notable risk factor for dyspepsia. Among patients with bile acid reflux, common endoscopic findings include mucosal erythema, the presence of bile acid on the mucosa, erosions, hyperrugosity, and gastric mucosal atrophy. This study aims to elucidate the association between bile acid levels in gastric fluid and the degree of gastric mucosal damage.Methods: This cross-sectional study involved dyspeptic patients who underwent endoscopic examination at Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital. Bile acid analysis was conducted through the enzymatic calorimetric method, while assessment of mucosal damage relied on the Lanza score, evaluated independently by two observers. Mucosal damage severity was categorized as either mild (score 0-2) or severe (score 3-5). Statistical analyses included Cohen’s kappa for interobserver agreement, bivariate analysis, and logistic regression.Results: Of the 99 subjects involved in the study, 58.6% were male. H. pylori antibodies were detected in 21% of the participants, while 48% exhibited a pH below 2.77. Additionally, 48% reported a history of NSAID consumption. The mean bile acid level in gastric fluid was 156.07 μmol/L, with a median of 170.09 μmol/L (categorized as high if ≥ 170.09 μmol/L, and low if 170.09 μmol/L). During endoscopic examination, mild mucosal damage was observed in 61%, and severe damage in 39% (kappa 1, P 0.001). A statistically significant relationship between gastric f luid bile acid levels and mucosal damage was evident (P 0.05).Conclusion: This study concludes that there was a relationship between the level of bile acid in gastric fluid and the degree of mucosal damage.